Perspectives on The Rise and Fall of American Growth - Gordon, Robert J. (American Economic Review, 2016)
This paper summarizes the book and assesses the reviews contained in the four contributed papers. Gregory Clark provides convincing arguments that extend the book's forecast that future technological change will be slower. Nicholas Crafts shows declining mortality and shorter work hours greatly increase welfare-augmented TFP growth during 1929-50. Benjamin Friedman points out that optimism about future technological change casts doubt on future employment growth, while technological pessimism implies employment optimism. Daron Acemoglu and co-authors emphasize the institutional environment that influences the timing and magnitude of innovation.